(untitled) (World Bulletin of Education and Learning, 2025)
This article examines practical and effective methods for improving writing skills among school students. Writing is an essential component of academic development, helping learners express ideas clearly, think critically, and communicate effectively. Therefore, strengthening students’ writing abilities requires a well-structured and supportive approach in the classroom. The article highlights several key strategies that teachers can use to enhance writing proficiency. Guided writing is emphasised as one of the most useful methods, as it allows teachers to model sentence structure, paragraph organisation, and the overall writing process. By observing these steps, students gain a clearer understanding of how to plan and develop their ideas. Peer feedback is another important technique that encourages collaboration and helps students evaluate their own writing through reviewing their classmates’ work. Vocabulary enrichment activities also contribute significantly to better writing. A wider range of words enables students to express themselves more accurately and creatively. In addition, the article stresses the importance of process-based writing, which includes drafting, revising, and editing. This approach teaches students that improvement comes through practice and reflection, not through producing a perfect text on the first attempt. The article concludes that consistent practice, supportive teaching strategies, and interactive learning can greatly improve students’ writing skills.